Nganjuk Regency Government Strategy to Increase Local Economic Growth Through Agricultural Sector Development - Destara (Konsultan Surya Buana, 2024)
The economic growth of Nganjuk Regency, which has experienced a decline, causing poverty levels to rise, is accompanied by the role of the agricultural sector which dominates there as the main economic driving sector. This research aims to determine the efforts made by the Nganjuk Regency Government to increase local economic growth through developing the agricultural sector. The method used in carrying out this research is qualitative descriptive analytical. The data obtained from this research is primary data in the form of interviews and secondary data as supporting data. The results of this research reveal that the Nganjuk Regency government is making efforts through programs to provide infrastructure, manage agricultural disasters, optimize agricultural potential through rehabilitation, intensification and crop diversification. This effort has had an impact on the production of superior commodities, some of which have increased and some of which have unstable production levels. Apart from that, the efforts made also have an impact on decreasing regional income from the agricultural sector, however in terms of welfare in 2022 the Farmer's Exchange Rate is still categorized as having a surplus in general. So it can be said that the strategy implemented does not have a positive impact on regional income from the agricultural side. The limitation of this research is the lack of other supporting data to measure the success of the program. Future research needs to initiate the collection of complete data.Keywords: Agriculture, Growth, Economy, Development